Ciclo gonádico del ostión americano Crassostrea virginica (Lamellibranchia: Ostreidae) en Mecoacán, Tabasco, México - George-Zamora, Arturo (2003)
The american oyster Crassostrea virginica is exploited along Gulf of Mexico. This resource represents a job source and incomes for fishermen. In Mexico the production is supported by Tabasco state, the first producer. However, the mexican landings of this bivalve had been dropped about 40% last ten years. By 1999, Tabasco presents a unique ban season fishery of oysters. This season was based in evaluation of gonadal development by visual observations of color and texture, larvae and seeds abundance. In 2000, the government set up two ban seasons in terms of evaluation of populations every year, without gonadal analysis. In general, exists different spawning seasons for american oyster, in accordance with the environmental conditions. It is necessary to establish a ban season according to reproductive cycle. This study presents the gonadic cycle for an oyster population of Mecoacán lagoon along a year. It was defined five phases of the gonad development: resting, gametogenesis, mature or ripe, spawn and post spawn. Gametogenesis is present all the year, except December. The spawning activity was detected all year, except July and August. The ripe phase presented maximum values in August and December. It was proposed a modification of the ban seasons from April 15 - May 30, and September 15 - October 30 to March 15 - May 15 and September 1 - October 30, respectively, according to gonadic cycle obtained in this work. This modification would to avoid capture mature organisms (ready to spawn).